Neurovascular Uncoupling in Schizophrenia: A Bimodal Meta-Analysis of Brain Perfusion and Glucose Metabolism - Sukumar, Niron; Sabesan, Priyadharshini; Anazodo, Udunna; Palaniyappan, Lena (Frontiers in Psychiatry, 2020)
The use of modern neuroimaging approaches has demonstrated resting-state regional cerebral blood flow (rCBF) to be tightly coupled to resting cerebral glucose metabolism (rCMRglu) in healthy brains. In schizophrenia, several lines of evidence point towards aberrant neurovascular coupling, especially in the prefrontal regions. To investigate this, we used Signed Differential Mapping to undertake a voxel-based bimodal meta-analysis examining the relationship between rCBF and rCMRglu in schizophrenia, as measured by Arterial Spin Labeling (ASL) and 18Flurodeoxyglucose Positron Emission Tomography (FDG-PET) respectively. We used 19 studies comprised of data from 557 patients and 584 controls. Our results suggest that several key regions implicated in the pathophysiology of schizophrenia such as the frontoinsular cortex, dorsal ACC, putamen, and temporal pole show conjoint metabolic and perfusion abnormalities in patients. In contrast, discordance between metabolism and perfusion were seen in superior frontal gyrus and cerebellum, indicating that factors contributing to neurovascular uncoupling (e.g. inflammation, mitochondrial dysfunction, oxidative stress) are likely operates at these loci. Studies enrolling patients on high doses of antipsychotics had showed larger rCBF/rCMRglu effects in patients in the left dorsal striatum. Hybrid ASL-PET studies focusing on these regions could confirm our proposition regarding neurovascular uncoupling at superior frontal gyrus in schizophrenia.